2016
DOI: 10.18203/2349-3259.ijct20162799
|View full text |Cite
|
Sign up to set email alerts
|

A study on antibacterial effect of grape seed extracts in common clinical and drug resistant isolates

Abstract: <p class="abstract"><strong>Background:</strong> Grape seeds are proposed to have antimicrobial activity, antioxidant effect and various other benefits to mankind. A study was done to assess the antibacterial effect of grape seed extract against common clinical isolates and drug resistant pathogenic strains.</p><p class="abstract"><strong>Methods:</strong> Grape seed extract prepared was investigated for its antibacterial effect against 65 bacterial isolates obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
7
1
Order By: Relevance
“…Adámez, et al, (2012) and Butkhup et al, (2016) also indicated the GSE more effective on Gram-positive bacteria. The results provide evidence that the grape seed extract could be a potential antibacterial agent and this effect can further be made evident with improved methodologies (Kandasamy et al, 2016). These strong sensitivities of the bacteria to GSE may be related to the inhibition of the hydrolytic enzymes (proteases and carbohydrolases) or other interactions capable of inactivating microbial adhesins, transport proteins and cell envelope due to the composition of extract in procyanidines, as stated by Cowan (1999).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Adámez, et al, (2012) and Butkhup et al, (2016) also indicated the GSE more effective on Gram-positive bacteria. The results provide evidence that the grape seed extract could be a potential antibacterial agent and this effect can further be made evident with improved methodologies (Kandasamy et al, 2016). These strong sensitivities of the bacteria to GSE may be related to the inhibition of the hydrolytic enzymes (proteases and carbohydrolases) or other interactions capable of inactivating microbial adhesins, transport proteins and cell envelope due to the composition of extract in procyanidines, as stated by Cowan (1999).…”
Section: Discussionmentioning
confidence: 65%
“…It might also be related to the presence of tannins which has the ability to inactive microbial adhesions, enzymes and cell envelope transport proteins, their complexity with polysaccharide and their ability to modify the morphology of microorganisms. Therefore, this observation is suggestive of the antibacterial effect of grape seed extract (Kandasamy et al, 2016). According to Shrestha (2012), the structureactivity correlation assays showed that the hydroxyl group of the phenolic compound was found to be effective against E. coli and the benzene ring was effective against S. aureus.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The specimens were processed in culture plates and the pathogens were isolated and identified by standard biochemical tests. Mueller-Hinton agar [15] was used Agar dilution methods from low dose to high dose (20, 30, 40, 50, 60 mg) to determine the antibacterial effect of cranberry fruit extract and the routinely used antibiotics, Linezolid for MRSA strains and Meropenem for ESBL producing E. coli organisms were used for comparison [16].…”
Section: Isolation Of Bacteria From Clinical Specimensmentioning
confidence: 99%